2018
DOI: 10.1051/ctv/20183302116
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and sensory characterization of the aroma of ‘Chardonnay’ musts fermented with different nitrogen sources

Abstract: This work studies the influence of two different nitrogen sources added to the must on aromatic series and sensory profile of ‘Chardonnay’ wines. Volatile compounds were classified into six odorant series and the total intensities for every aromatic series were calculated as sum of the OAV of each one of the compounds assigned to these series. Sensory profile was defined by quantitative descriptive sensory analysis. The fruity, floral and sweet series are the ones most strongly contributing to the aroma of ‘Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The specific m / z fragment for each compound was used for the quantification by GC-MS, using the internal standard method. The concentration of non-available commercial compounds was expressed as equivalents of the internal standard obtained by normalizing the peak area of each compound to that of the internal standard and multiplying by the internal standard concentration [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The specific m / z fragment for each compound was used for the quantification by GC-MS, using the internal standard method. The concentration of non-available commercial compounds was expressed as equivalents of the internal standard obtained by normalizing the peak area of each compound to that of the internal standard and multiplying by the internal standard concentration [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Izquierdo-Canãs et al showed temperature of alcoholic fermentation had a significant impact on the lactone concentration in Petit Verdot red wines. 131 γ-Hexalactone, γ-nonalactone, γ-decalactone, and δ-decalactone were quantified in the resulting wines. The most significant differences were observed in δ-decalactone concentration, which increased from 53 μg L −1 in the 17 °C sample to 90 μg L −1 in the 25 °C sample.…”
Section: Lactones In Grapes and Winementioning
confidence: 99%
“…This suggests that fermentation temperature likely does have a significant impact on lactone concentrations in wines, possibly through modifications in yeast metabolism. 131 ■ ANALYTICAL METHODS: EXTRACTION AND…”
Section: Lactones In Grapes and Winementioning
confidence: 99%
“…The nitrogenous compounds in fruit wine are higher than in other fermented beverages (65). The aromatic complexity of wine is enhanced when organic nitrogen sources are added to the must before fermentation (66). The aromatic compounds that are influenced by nitrogenous compounds in wine are listed in the Table 2 (66)(67)(68).…”
Section: Effects Of Nitrogenous Compounds On Fermented Liquormentioning
confidence: 99%
“…The aromatic complexity of wine is enhanced when organic nitrogen sources are added to the must before fermentation (66). The aromatic compounds that are influenced by nitrogenous compounds in wine are listed in the Table 2 (66)(67)(68). Table 2 shows that the esters are clearly affected by nitrogenous compounds.…”
Section: Effects Of Nitrogenous Compounds On Fermented Liquormentioning
confidence: 99%